Research and extension needs of woody plant growers : a history and survey to describe the woody plant industry : a thesis presented in partial fulfilment of the requirements for the degree of Master of Horticultural Science in Horticultural Management at Massey University - Cameron, Ewen Alistair (Massey University, 1993)
Woody plant growing businesses are a major part of New Zealand's nursery industry. Neither these businesses nor their participants have been well described. Research and extension services have been provided at low cost to the growers. Farming Systems Research and Extension methodology was used to describe the membership of the woody plant industry and their businesses. The constraints to growth, and opportunities for business development were also described. An initial identification of the research and extension priorities was also made. The method used to obtain this information was by postal survey. The industry was found to contain many more participants than previous estimates had indicated. The industry was also found to be very diverse. Businesses ranged from those employing no additional staff to those employing more than 100. Although the mean business size was 1 hectare, the smallest business was based on a small laboratory (0.1ha) and the largest covered more than 150ha. Almost half the respondents were specialist woody plant producers involved only with woody plant production. However, many of the more diversified businesses, which were involved with other nursery crop enterprises, earned more than 76% of their income from woody plants. Within each woody plant enterprise growers described a wide range of crop specialisations. Few businesses were more than 15 years old and most had been set up by the respondents. Although many growers had good educational background many had trained in other areas before entering the woody plant industry. The more recently established businesses were more likely to be involved in many enterprises. Most of the growers traded solely on the local market and only 10% reported upon the direct export of their crops. The local market was described as being over-supplied with inferior quality products. Although few growers declared they had any debt many described finance as the factor most likely to inhibit expansion of their businesses. Most growers described business, managerial, market and personnel issues as being the most serious challenges to their businesses. Although these business management challenges provided the issues which were of the highest priority in terms of research need, most growers thought a range of technical issues should be on their research agenda. Business management needs were likely to be of the highest priority for industry participants. Since business information is available cheaply from many sources, the provision of such information is not likely to be financially rewarding for research and extension providers. In a user pays environment, to ensure that the needs of both woody plant industry participants and research and extension service providers are met, research and extension activities should be targeted to the needs of growers. Growers must be prepared to pay the full cost of research and extension services provided for them. Proposals for the development of strategies for mutually beneficial research and extension are made using the principle of FSR/E methods, ie., by involving the growers to a larger extent in the development of the research agenda. Hence growers are more likely to be willing to pay for work that is tailored to their needs.
Keywords: Nurseries (Horticulture); Nursery growers, New Zealand; Nursery business management; Woody plants; Nursery industry, New Zealand